P415 NEUROGENIC STRESS CARDIOMYOPATHY. (18th May 2022) - De Sanctis, G; Rizzo, M; De Pascali, I; Guasti, S; Chianta, V; Bruno, N; Monzo, L; Tanzilli, G
Abstract: Case Report: Caucasian 84–years–old woman was found on the floor at her house and was brought to the ED of Policlinico Umberto I with the diagnosis of cranial trauma following a syncope. A head CT showed right paramedian fracture of the occipital bone, left frontal subarachnoid hemorrhage and left frontal subdural hemorrhage. The neurosurgeon gave no indication to urgent evacuation of the hemorrhage. Then elevation of cardiac enzymes and ST–segment elevation at the EKG were found but due to the state of the patient a coronary angiography was not performed and the patient was transferred to the CCU. The patient was hemodynamically stable with right hemiplegia. The EKG showed rapid ventricular rate atrial fibrillation with ST segment elevation in inferior and lateral leads with T wave inversion in the same leads and elevated serum troponin levels. ETT showed: EF 30% with a global reduction of left ventricular systolic function with diffuse akinesis. Intravenous therapy with mannitol and corticosteroids for perilesional oedema was started. Beta blockers and a class III antiarrhythmic drug were also started, but hemodynamic conditions declined and acute kidney failure occurred with progressive hypotension followed by cardiogenic shock. The patient had an episode of nonsustained ventricular tachycardia treated with antiarrhythmic drugs and magnesium sulfate. The EKG started to show a normalization of the repolarization phase with regression of ST segment elevation and persistent T wave inversion.The patient's neurological conditions were complicated with epileptic seizures.On the fifth day of hospitalization the TTE revealed a slight improvement of global systolic function and the presence of an apical thrombotic apposition.The patient's clinical conditions worsened and led to exitus. Discussion: The interpretation of this patient's history was made more difficult by the lack of witnesses of the trauma.The patient's age, her history of hypertension and the presence of regional wall motion abnormalities at the TTE suggested the presence of CAD. On the other side the atrial fibrillation could hint a primitive cerebral event. This case report shows the potentially severe cardiac manifestations of cerebral hemorrhage and the necessity to consider cerebrovascular events as the cause of EKG changes mimicking a myocardial infarction, cardiac enzymes elevation and ventricular wall motion abnormalities, in order to avoid inappropriate or delated therapies.